2018
DOI: 10.1159/000493133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Choice of IGF-I Assay and Normative Dataset on the Diagnosis and Treatment of Growth Hormone Deficiency in Children

Abstract: Background: The analysis of insulin-like growth factor I (IGF-I) is an important tool for pediatricians in the diagnosis and treatment of growth hormone deficiency in children. However, significant differences exist in IGF-I assays and normative datasets, which can have important clinical consequences. Methods: IGF-I analyses were performed using the IDS-iSYS platform on 1,897 samples from pediatric patients (0.5–18 years old). Z-scores were calculated based on normative IGF-I data from Bidlingmaier et al. (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This discordance might have important implications for clinical practice. This does not mean that an assay is better than another, which cannot be indicated by this study, this only means that the use of different IGF-1 assays for a single patient might affect treatment decisions and dose adjustments in children and adults, especially when IGF-1 levels are borderline (6,11).…”
Section: Discussionmentioning
confidence: 87%
“…This discordance might have important implications for clinical practice. This does not mean that an assay is better than another, which cannot be indicated by this study, this only means that the use of different IGF-1 assays for a single patient might affect treatment decisions and dose adjustments in children and adults, especially when IGF-1 levels are borderline (6,11).…”
Section: Discussionmentioning
confidence: 87%
“…IGF-1 concentrations change with age and gender so that normative data have been determined from large numbers of healthy children and adolescents ( 87 ). This enables appropriate correction to provide SDS values, although the correct normative data should be used because diverse cohorts may give different reference measurements ( 90 , 91 ). Such differences may give clinically relevant variation when used to establish a diagnosis of GH deficiency ( 92 ).…”
Section: Interpretation Of Igf-1 Datamentioning
confidence: 99%
“…Dear Editor, Three recent publications (1,2,3) have reported that the differences in IGF-1 normative data significantly impact the classification of patients with growth hormone (GH) excess and deficiency disorders in such a way that clinical performance is severely flawed. This concerns not only pediatric but also adult patients.…”
mentioning
confidence: 99%
“…Two extensive multicenter publications reporting IGF-1 reference values including SDS calculation, stressed the tremendous efforts needed to establish age-and sex-dependent normative data for IGF-1, the limited comparability of IGF-1 assays and the differences between various normative datasets available (5,6). However, despite all efforts, recent reports have shown that variation in IGF-1 normative data still impacts the classification of patients with GH-related disorders, not only in pediatric patients (GH deficiency) but also in adult acromegaly patients (1,2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation